Analisis Program Galeri Budaya Nusantara (GAYARA) Radio Republik Idonesia dalam Meningkatkan Pemahaman Masyarakat terhadap Budaya Nasional - Mukhlizar Mukhlizar; Chantika Lestari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to find out how the analysis of GAYARA broadcast programs increases people's understanding of national culture in terms of pre-production, production, and post-production processes and also to find out how people understand after hearing GAYARA broadcast programs. The research method uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Sources of research data are taken from primary data sources and secondary data sources. The results of the study indicate that the process of implementing the GAYARA broadcast program production has been going quite well and the listeners of the GAYARA broadcast program know and understand more about the culture in Indonesia. The conclusion of the research is that the GAYARA broadcast program has the aim of providing information and understanding related to national culture to the public, one of which is regarding the art culture of madihin and messages of mande. Keywords: Community Understanding, National Culture.